Mikroutopia w praktyce: sztuka indygeniczna i strategie wydawnicze Tara Books w Indiach - Sikorska, Magdalena (Zagadnienia Rodzajów Literackich, 2025)
This article explores the publishing practices of the Chennai-based independent publisher Tara Books as a unique form of “publishing microutopia” that promotes indigenous art from India. Drawing on Ewa Domańska’s concept of microutopia understood as small-scale, localized experiments in creating resilient communities, this study examines how Tara Books’ aesthetic, ethical, and political commitments foster new modes of visibility and empowerment for marginalized communities. The article focuses on the collaborative production process behind several titles authored and illustrated by Gond, Warli, and Patua artists, analyzing both visual content and editorial framing. These works are interpreted not only as artistic artifacts but also as forms of decolonial knowledge production and cultural resistance. The author argues that Tara Books creates a space where indigeneity is not merely represented but re-enacted through design, narrative, and materiality, thereby embodying the microutopian potential of publishing. By combining insights from visual studies, postcolonial theory, and historiography, the article contributes to current debates on art, activism, and the politics of publishing. It proposes that publishing work, especially when rooted in feminist, egalitarian, and participatory values, can serve as a critical tool in reimagining social and historical futures.